Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawan Pada Perusahaan Daerah Air Minum (PDAM) Kabupaten Banggai: The Influence of Work Environment on Employee Performance at Regional Water Company Banggai Regency - Jalaludin; Sri Mulyaningsih Kamaru; Liswan Rusman (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2022)
The work environment is an important factor that can affect employee performance. The existing work environment will provide different perceptions of employees in their performance. The problem is whether the work environment has a significant effect on employee performance at the Regional Water Company Banggai Regency. The sampling technique in this study used a simple random sampling technique with a total sample of 39 employees of the Regional Water Company Banggai Regency. The results of this study were obtained using simple linear regression analysis with the formula y = a + bx, this equation shows a positive and unidirectional relationship. Calculation of the correlation coefficient shows that the Work Environment (X) and Employee Performance (Y) have a strong relationship. The value of the coefficient of determination (r2) with the variable (x) work environment has an influence on the variable (y) employee performance, while the rest is caused by other factors outside this study. Hypothesis testing shows the calculated T value, this proves that there is a significant effect between the work environment variable (X) on the employee performance variable (Y).